2021
DOI: 10.3390/plants10091913
|View full text |Cite
|
Sign up to set email alerts
|

Germination and the Initial Seedling Growth of Lettuce, Celeriac and Wheat Cultivars after Micronutrient and a Biological Application Pre-Sowing Seed Treatment

Abstract: Seed treatments with zinc, boron, biostimulant Coveron and MIX (zinc + boron + Coveron) were applied to three lettuce and three celeriac cultivars. Seeds of three wheat cultivars were treated under laboratory conditions with Trichoderma harzianum and eight Bacillus spp. Seed germination, seedling growth, and the presence of the following pathogens were determined: Fusarium sp., Alternaria sp., Penicillium sp., and Mucor sp. The Coveron treatment was the most effective on lettuce seeds tested in the germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…More specifically, inoculation with T. harzianum enhanced phase III imbibitions; i.e., cell elongation followed by radicle protrusion [ 32 ]. The promotive effect of Trichoderma on wheat seed germination was attributed to increasing gibberellic acid (GA3) that boosts up the activity of hydrolytic and proteolytic enzymes acting to mobilize the food reserves from the cotyledons or endosperm [ 33 ]. Otherwise, Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, inoculation with T. harzianum enhanced phase III imbibitions; i.e., cell elongation followed by radicle protrusion [ 32 ]. The promotive effect of Trichoderma on wheat seed germination was attributed to increasing gibberellic acid (GA3) that boosts up the activity of hydrolytic and proteolytic enzymes acting to mobilize the food reserves from the cotyledons or endosperm [ 33 ]. Otherwise, Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…This sample was obtained on 02/2021 and stored in a refrigerator for approximately 1 month. The germination conditions and experimental setup fall within the ranges and methods commonly utilized in seed germination tests for phytotoxicity [25,[28][29][30][31]. The trials were observed and measured for a period of 10 days, where each trial contained a buttercrunch lettuce seed inside of a Ziploc (San Diego, CA, USA) plastic sandwich bag with a 5.1 cm diameter circle of 2-ply paper towel for each seed, in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…This aligns with the compost tea results, as compost tea is largely composed of carbon and nitrogen species. The impact of certain micronutrients as well as biological treatments, comparable to PGPMs, were studied by Postic et al [28]. They determined that the biological treatment had the largest positive impact on germination percentage, followed by the mixed treatment and then the Zinc and Boron treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, diverse non-invasive optical spectroscopic techniques, including Raman and Elastic spectroscopy, have been used for plant physiology monitoring and assessment [39,40]. Alternatively, optical parameters, such as spectral reflectance indexes, have been employed as a non-invasive technique in lettuce physiology assessment [41][42][43][44][45][46] for early-stage detection of Botrytis cinerea after 12, 18, 36, 60 and 84 h [47].…”
Section: Introductionmentioning
confidence: 99%